2014
DOI: 10.1590/2317-1782/20142014050
|View full text |Cite
|
Sign up to set email alerts
|

Phonological and semantic verbal fluency: a comparative study in hearing-impaired and normal-hearing people

Abstract: Descritores

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
5
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 17 publications
3
5
0
1
Order By: Relevance
“…A study compared the performance of hearing-impaired and normal-hearing adults (18 to 60 years) on phonemic and semantic VF tests and found that both groups had a better performance in the semantic VF ("animals") in comparison with phonemic task ("F"). Moreover, the hearing-impaired group had a worse performance compared to the normal-hearing group (Santos et al 2014), which is in agreement with our findings. A possible explanation for these results is related to hierarchical memory organization of semantic VF category, which has subcategories ("pets", "zoo animals", "jungle animals", among others) allowing more words to be evoked (Azuma 2004;Santos et al 2014).…”
supporting
confidence: 92%
“…A study compared the performance of hearing-impaired and normal-hearing adults (18 to 60 years) on phonemic and semantic VF tests and found that both groups had a better performance in the semantic VF ("animals") in comparison with phonemic task ("F"). Moreover, the hearing-impaired group had a worse performance compared to the normal-hearing group (Santos et al 2014), which is in agreement with our findings. A possible explanation for these results is related to hierarchical memory organization of semantic VF category, which has subcategories ("pets", "zoo animals", "jungle animals", among others) allowing more words to be evoked (Azuma 2004;Santos et al 2014).…”
supporting
confidence: 92%
“…The subgroup of children with HL DLD retrieved a statistically significantly smaller number of animals compared with TD children. This is in line with Wechsler-Kashi et al (2014) and Santos et al (2014), who report children with HL to have difficulties with lexical access. This may indicate, as reported by Andersson (2002), that word retrieval difficulties are influenced by the combination of multiple factors.…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, a degraded auditory input is not necessarily enough for the children to exhibit word retrieval difficulties. As Santos et al (2014) and Coppens et al (2012) report, can degree of HL alone not explain the number of words retrieved by children with HL? It is often claimed that cognitive processing difficulties in children with HL are caused by an auditory perceptual deficit (Sahlén & Hansson, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a relationship between learning vocabulary and categorizing it in the lexicon, because categorization requires the existence of a mental representation of meaning, which is mapped to form lexical items. 1 The verbal fluency test can provide information about the storage capacity, the ability to retrieve information and evaluates strategies used to search for words.…”
Section: Introductionmentioning
confidence: 99%